A murine model of orthotopic periorbital subunit transplantation. Issue 2 (March 2017) - Gao, Bowen; Li, Bin; Li, Xinxin; Bae, Jinhong; Xiao, Kaiyan; Li, Qingfeng; Zhu, Hainan
Highlights: We established an orthotopic periorbital subunit transplantation model in the rat. The vascular distribution and innervation to the eyelid were recorded. The transplanted eyelids survived well and eyelid's function partially recovered. Abstract: Background: Conventional reconstructive methods fail to achieve satisfactory results in total eyelid defect cases. Vascularized composite tissue allotransplantation might provide both good appearance and function for these patients. We developed an orthotopic periorbital transplantation model in rats to facilitate further experimentation in this field. Methods: In anatomical studies, the vascular distribution to and innervation of the periorbital unit were identified and recorded. Then, according to the anatomical studies, eight orthotopic transplantations and two transplantations with pedicle ligation were performed. The posterior facial vein and the external carotid artery were selected as the graft pedicles, while the temporal and upper zygomatic facial nerves were used for graft innervation. All transplanted eyelids were assessed daily. Micro-CT scanning and hematoxylin and eosin staining of the grafts were performed 60 days after the operation. Results: In total, 90% of recipients tolerated the operation well. All grafts without pedicle ligation survived, and new hair growth was observed. The position of the eyelid was maintained, and eyelid function was partially restored. In the recipients with graft pedicle ligation, the grafts became necrotic and mummified within four to five days. Micro-CT of the surviving grafts showed a good blood supply, and histological staining revealed normal morphology. Conclusions: A periorbital subunit orthotopic transplantation model was established, which might facilitate future eyelid allotransplantation-related experimentation.